THE SOCIETAL AND LEGAL MISSING LINK IN PROTECTING A GIRL CHILD AGAINST ABUSE BEFORE AND AMIDST THE COVID-19 PANDEMIC IN NIGERIA - Paul Atagamen Aidonojie; Ong Argo Victoria (Jurnal Hukum, 2022)
It is a truism that several legal frameworks emphasize the right of a girl child in Nigeria. However, despite these legal frameworks that tend to recognize the rights and protection of the girl child, it has been observed that, before and during Covid-19 in Nigeria, there has been an increase of abuse of the girl child. The abuse of a girl child results from the Nigerian societal norms and legal framework missing link that downplay the protection of the girl child. It is concerning the above that this study adopts a hybrid research method, which includes a doctrinal and non-doctrinal approach in ascertaining the Nigerian societal norms and legal missing link concerning the protection of a girl child. Therefore, the study employs an online questionnaire survey sent to 322 respondents (randomly selected) who live in Nigeria to ascertain their view concerning the Nigerian societal norms and legal framework missing link concerning the protection of a girl child before and during the Covid-19. Therefore, the study found that, though there is a sufficient legal framework that provides for the protection of a girl child in Nigeria, the abuse of a girl child is on the increase. Therefore, it was concluded and recommended that for there to be effective care and protection of a girl child. There is a need for effective implementation of the relevant legal framework and eradication of all forms of legal technicalities that obstruct the cause of justice against the protection of a girl child. Furthermore, Government must re-orient most Nigerian society that places less emphasis on the rights of a girl child.Â